Covid-19 Containment Policies in Europe
XXIII, 307 p. 50 illus.
Keywords: This open access book examines the diverse strategies implemented by national and local European governments to contain the Covid-19 pandemic. Rather than focus on individual national case studies, it brings together leading scholars and policymakers to analyse the wide range of containment policies utilised across the continent at various levels of government. In doing so, the volume assesses Covid-19 crisis-management experiences to identify good practices based on comparative and fine-grained evidence. It argues that such a stock-taking exercise is crucial to better prepare European polities and societies for future crises, including climate change and environmental disasters. The book will appeal to scholars and students of public policy, crisis-management, public administration, international relations and comparative law. Clara Egger is Assistant Professor of Global Governance in the Department of Public Administration and Sociology, Erasmus School of Social and Behavioural Sciences, Erasmus University Rotterdam, the Netherlands Raul Magni-Berton is Professor of Political Science and Scientific Director at the European School of Political and Social Sciences, Lille Catholic University, France. Eugenie de Saint-Phalle is Lecturer at the University of Groningen, the Netherlands.